Evaluasi Skrining pada Pasien Karies Gigi dan Penyakit Periodontal di Puskesmas Lamteuba Kabupaten Aceh Besar - T Nazarullah; Radhiah Zakaria; Basri Aramico (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Oral health problems, particularly dental caries and periodontal disease, remain significant public health concerns. This study aimed to evaluate the implementation of oral health services at Lamteuba Community Health Center, Aceh Besar District, during the period 2023–2025. This study employed an evaluative design with a retrospective descriptive approach using secondary data obtained from dental clinic registers, oral health examination records, and procurement reports of dental materials and equipment. Data were analyzed descriptively. The results showed that the number of patient visits decreased from 355 visits in 2023 to 256 visits in 2024 and 137 visits in 2025. Dental caries cases declined from 258 cases in 2023 to 155 cases in 2024 and 64 cases in 2025. Similarly, periodontal disease cases decreased from 40 cases in 2023 to 27 cases in 2024 and 20 cases in 2025. In contrast, referrals increased from 1 case in 2023 to 5 cases in 2024 and 10 cases in 2025. Oral health services at Lamteuba Community Health Center have been implemented according to established procedures and demonstrated a decreasing trend in dental caries and periodontal disease cases. However, strengthening promotive and preventive activities, as well as expanding early detection coverage, is necessary to improve the effectiveness of oral health services.